Analisis Resepsi Mukbang Tanboy Kun : Studi pada Khalayak Remaja di Kota Denpasar - Putu Wulandari, Ni Luh; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2025)
The development of the internet resulted in various content being made on social media. One of the content created on social media is mukbang content. It is widely broadcast on social media such as YouTube. This phenomenon displays eating activities with large portions beyond the normal eating portions. One of the mukbang actors who actively uploads his mukbang content on YouTube is Tanboy Kun. This research aims to discover the meaning of messages teenagers receive in Denpasar City after watching Tanboy Kun's mukbang videos on the YouTube channel. To achieve the research objectives, the theory used in this research is Stuart Hall Reception Theory with analysis, namely Stuart Hall Reception Analysis. The type of research used is descriptive-qualitative research. The study results show that, on average, the informants fall into the Dominant-Hegemonic and Negotiated Position categories.